Navigation of lead extraction—is it possible? Impact of preprocedural electrocardiogram-triggered computed tomography on navigation of lead extraction. (30th March 2018) - Vogler, Julia; Pecha, Simon; Azarrafiy, Ryan; Castro, Liesa; Deuschl, Florian; Spink, Clemens; Linder, Matthias; von Hehn, Ulrike; Willems, Stephan; Reichenspurner, Hermann; Gosau, Nils; Hakmi, Samer
Abstract: OBJECTIVES: As the number of transvenous lead extractions continues to increase, preprocedural protocols for this procedure must be assessed. The objective of this study was to determine whether an electrocardiogram (ECG)-triggered computed tomography (Et-CT) with three-dimensional (3D) reconstructions could aid lead extractors in choosing the optimal tools to improve procedural success and avoid complications. METHODS: In this study, 31 patients scheduled for transvenous lead extraction underwent a preprocedural Et-CT between January 2016 and May 2017. Both 3D-reconstructions and the two-dimensional files were reviewed for possible lead adhesions, calcifications, migrations or perforations. RESULTS: Mean age was 46.7 ± 14.0 years. Seventy-one percent of patients were men, and 29.0% had undergone prior cardiac surgery. Indications for extraction included infection ( n = 18, 58.1%), lead dysfunction ( n = 8, 25.8%), upgrade ( n = 3, 9.7%), severe tricuspid regurgitation ( n = 1, 3.2%) and superior vena cava occlusion ( n = 1, 3.2%). Eighteen patients had an implantable cardioverter defibrillator (58.1%). Sixty-eight of 70 targeted leads were extracted with a mean of 2.2 leads per patient and an average lead age of 109.3 ± 58.7 months. Et-CT files supported transvenous lead extraction by revealing possible adhesions in 16 patients, 5 perforations and 2 venous occlusions. Lead extraction was performed using the excimer laser, mechanical tools and femoral snares. Complete procedural success was achieved in 93.5% ( n = 29) of cases. Clinical success was 100%, and intraoperative mortality was 0%. CONCLUSIONS: A preprocedural Et-CT with 3D reconstructions can help to visualize lead alignment and identify abnormalities that may foreshadow procedural difficulties. A preprocedural Et-CT may therefore aid lead extractors in choosing the optimal extraction tool and strategy.